No significant drug−drug interaction between oral TAF‐based PrEP and feminizing hormone therapy among transgender women in Thailand: the iFACT‐3 study - Hiransuthikul, Akarin; Thammajaruk, Narukjaporn; Kerr, Stephen; Janamnuaysook, Rena; Nonenoy, Siriporn; Hongchookiat, Piranun; Trichavaroj, Rapee; Tawon, Yardpiroon; Boonruang, Jakkrapatara; Teeratakulpisarn, Nipat; Cressey, Tim R.; Anderson, Peter L.; et al. (Journal of the International AIDS Society, 2025)
Introduction Concerns regarding potential drug−drug interaction (DDI) between feminizing hormone therapy (FHT) and HIV pre‐exposure prophylaxis (PrEP) may hinder PrEP use among transgender women. We assessed the potential DDI between FHT and emtricitabine‐tenofovir alafenamide (F/TAF)‐based PrEP among transgender women. Methods Transgender women without HIV who never underwent orchiectomy were enrolled between January and February 2022. Oral FHT (oestradiol valerate 2 mg and cyproterone acetate 25 mg) was initiated at baseline and continued until week 9, while oral PrEP (F/TAF 200/25 mg) was initiated at week 3 and continued until week 12. Intensive blood sampling was performed at weeks 3 and 9 to assess the impact of PrEP on FHT; and weeks 9 and 12 to assess the impact of FHT on PrEP. Pharmacokinetics (PKs) of plasma oestradiol (E2), TAF, tenofovir (TFV) and emtricitabine (FTC); urine TFV and FTC; and tenofovir‐diphosphate (TFV‐DP) and emtricitabine‐triphosphate (FTC‐TP) in peripheral blood mononuclear cells (PBMCs) and rectal tissues were assessed. Results Eighteen participants completed all PK visits. No significant differences in PK parameters for plasma E2, TAF and TFV were observed with FHT and F/TAF administration. The geometric mean of FTC AUC0−24 at week 9 was 9% lower than at week 12, but the 90% CI (0.88−0.95) remained within the 80–125% range. There were no significant differences in PBMCs and rectal tissues TFV‐DP and FTC‐TP concentrations when F/TAF was administered with FHT. Conclusions No bidirectional clinically significant DDI between FHT and F/TAF‐based PrEP was observed across systemic and local tissue anatomical compartments, supporting the use of oral F/TAF‐based PrEP among transgender women. Clinical Trial Number NCT04590417